PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR MELALUI MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) PADA MURID KELAS IV UPT SD NEGERI LATSARI TUBAN - Nadita Fadila Hasyim; Sri Cacik; Tri Eko Baktiono (STKIP Subang, 2026)
This classroom action research was motivated by the low mathematics learning outcomes regarding the topic of 2D shapes among fourth-grade students at UPT SD Negeri Latsari Tuban, as evidenced by suboptimal achievement of learning mastery. This situation highlighted the need to implement a learning model capable of enhancing student engagement, motivation, and learning outcomes. The study aimed to improve mathematics learning outcomes on the topic of 2D shapes through the implementation of the Teams Games Tournament (TGT) cooperative learning model. A Classroom Action Research (CAR) design was employed, conducted over two cycles, each comprising the stages of planning, action implementation, observation, and reflection. The study took place in the fourth-grade class at UPT SD Negeri Latsari Tuban. Implementation occurred in two cycles: Cycle I on Thursday, April 23, 2026, and Cycle II on Friday, April 24, 2026. The results indicate that the Teams Games Tournament (TGT) cooperative learning model successfully improved student learning outcomes. In Cycle I, the percentage of students achieving mastery was 64.29%, while 35.71% did not achieve mastery. In Cycle II, the percentage of students achieving mastery rose to 92.86%, while 7.14% did not achieve mastery. The percentage of learning mastery increased by 28.57%. These findings demonstrate that the Teams Games Tournament (TGT) cooperative learning model is effective in improving mathematics learning outcomes regarding 2D shapes by fostering collaborative, competitive, and enjoyable learning activities.